The impact of the Covid-19 pandemic on dengue notification in Brazil (Research, Society and Development, 2022)
Dengue is an acute systemic febrile disease of viral origin, transmitted during hemophagy by the Aedes aegypti mosquito. Unlike dengue, Covid-19 has high transmissibility and is the highest indicator of mortality. Brazil, in addition to facing Covid-19, has also faced the dengue epidemic since 1986, failures in actions to control the mosquito vector contribute to the increase in cases. Thus, this research is important because it seeks to analyze the impact of the Covid-19 pandemic on the notification of Dengue cases, by comparing the years 2019 and 2020 in Brazil. This is a descriptive, retrospective and analytical epidemiological study on compulsory notifications of dengue, prepared using secondary data, from 2019 to 2020. During the analyzed period, 2,510,586 notifications were recorded in the disease information system of dengue notification in Brazil. With regard to geographic regions, the largest number of notifications is concentrated in the Southeast region. Regarding age group, patients aged 20 to 39 years were the most affected. Regarding gender, females predominated. As for the informed ethnicity of dengue notifications, the highest number of cases prevailed in patients of white ethnicity. With regard to geographic regions, the largest number of notifications is concentrated in the Southeast region. With this, it is possible to point out that dengue notifications as a public health problem that deserve the attention of the government and Brazilian society in general.